Transversely isotropic hyperelastic-viscoplastic model for glassy polymers with application to additive manufactured photopolymers. (May 2016) - Zhang, Pu; To, Albert C.
Abstract: A typical feature of additive manufactured photopolymers is that their mechanical behavior depends on the printing direction. Hence, this work aims at developing a material model to predict the inelastic deformation and failure of glassy polymers with such an effect. To achieve this goal, a transversely isotropic hyperelastic-viscoplastic model is proposed, which considers the effects of strain rate, pressure, temperature, and printing direction. In addition, a modified Tsai-Wu failure criterion is proposed to predict the macroscopic failure of glassy polymers with strain softening. The proposed model is applied to simulate the deformation and failure of additive manufactured lattice structures. Experimental and simulation results indicate that the mechanical behavior of additive manufactured lattice structures depends on not only the lattice orientation but also the printing direction. Highlights: The printing direction effect is studied and modeled for photopolymers. A transversely isotropic hyperelastic-viscoplastic model is developed. The plastic model considers material anisotropy and pressure-sensitivity. A failure criterion is proposed for glassy polymers with strain softening.